Call me maybe: experimental evidence on frequency and medium effects in microenterprise surveys - Garlick, R; Orkin, K; Quinn, S (Oxford University Press, 2019)
This study analyzes the effects of differences in survey frequency and medium on microenterprise survey data. A sample of enterprises were randomly assigned to monthly in-person, weekly in-person, or weekly phone surveys for a 12-week panel. The results show few differences across the groups in measured means, distributions, and deviations of measured data from an objective data-quality standard provided by Benford’s Law. However, phone interviews generated higher within-enterprise variation through time in several variables and may be more sensitive to social desirability bias. Higher-frequency interviews did not lead to persistent changes in reporting or increase permanent attrition from the panel but did increase the share of missed interviews. These findings show that collecting high-frequency survey data by phone does not substantially affect data quality. However, researchers who are particularly interested in within-enterprise dynamics should exercise caution when choosing survey medium.